Isolation and identification of streptococcus equi equi in guttural pouch in horses - Alias, Norwahidah (2015)
Guttural pouch is a paired extension of auditory tube which is known to be one of the structures of upper respiratory tract in horses. Any changes in the microflora along the respiratory tract can lead to respiratory disease under certain circumstances. There is limited information on bacteria isolates in guttural pouch of horses from tropical countries and this study was conducted to identify Streptococcus equi equi and other normal flora in the guttural pouch of horses. A total of 4 euthanized horses were used in this study and surgical approach of Viborg’s triangle technique was performed to get access to the guttural pouch. A sterile PBS was instilled into the guttural pouch to obtain the samples. The samples were cultured onto blood agar and McConkey agar and identified by a series of biochemical test. Seventeen isolates obtained which comprised of 9 species of bacteria and they were identified as Staphylococcus aureus (17.65%), Klebsiella pneumonia (17.65%), Stapyhlococcus intermedius (11.76%), Pasturella spp. (11.76%), Corynebacterium spp. (11.76%), Actinomyces spp. (11.76%) and Pasturella caballi (5.88%), Moraxella equi (5.88%), and Rhodococcus spp. (5.88%). However, Streptococcus equi equi was not among the isolates obtained. The Polymerase Chain Reaction (PCR) employed confirmed, negativity for Streptococus equi equi. Based on the findings of this study, it was concluded that several bacterial flora reside in the guttural pouch in apparently healthy horses and majority of bacteria are similar with those in upper respiratory tract reported in temperate countries which could become pathogenic in immunocompromised or stressed horses.